2022
DOI: 10.1097/md.0000000000028789
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of necrotizing enterocolitis in newborns with low birth weight

Abstract: There are needs to investigate the influencing factors of necrotizing enterocolitis (NEC) in low birth weight (LBW) newborns, to provide insights into the clinical management of NEC.This study was a retrospective cohort study. Infants admitted to our hospital from January 1, 2019 to June 30, 2021 were selected. The clinical characteristics of NEC and no-NEC infants were evaluated. Logistic regression analyses were conducted to assess the risk factors of NEC in LBW infants.A total of 192 LBW infants were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
2
5
0
2
Order By: Relevance
“…This study reported that approximately 30% of very low birth weight infants experienced NEC, whereas the mortality rate for NEC was 22%. These results are consistent with those found in other studies ( 3 , 24 ), thus supporting the fact that NEC is still a threat to be aware of.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study reported that approximately 30% of very low birth weight infants experienced NEC, whereas the mortality rate for NEC was 22%. These results are consistent with those found in other studies ( 3 , 24 ), thus supporting the fact that NEC is still a threat to be aware of.…”
Section: Discussionsupporting
confidence: 93%
“…Based on our nutrition protocol, enteral nutrition was given using human milk or preterm formula if human milk was not available. However, previous studies have shown that exclusive breastfeeding is a protective factor against the occurrence of NEC (3,22). Most of the very low birth weight infants born in our hospital received enteral nutrition which was a combination of breast milk and premature formula because their mother was still critically ill.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This meta-analysis showed that MSAF, history of antibiotic use and preterm infection were risk factors for NEC in preterm infants. Chen et al [ 45 , 54 , 63 ] also found that MSAF was an independent risk factor for NEC in preterm infants. The inhalation of amniotic fluid contaminated with meconium in utero in preterm infants can lead to the multiplication of intestinal pathogens and early infection [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the incidence of the disease reaches up to 13% of newborns at ≤33 weeks of gestation or babies with birth weights ≤2500 g and mortality rates between 30-50%. Finally, NEC occurs less often after ≥35 weeks of gestation [12][13][14]. Symptoms in premature infants and the time of onset, for the most part, are inversely proportional to gestational time (i.e., the earlier the newborn, the more obvious the signs).…”
Section: Introductionmentioning
confidence: 99%